2004
DOI: 10.1152/ajpheart.00058.2004
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial neovascularization by bone marrow angioblasts results in cardiomyocyte regeneration

Abstract: , and S. Itescu. Myocardial neovascularization by bone marrow angioblasts results in cardiomyocyte regeneration. Am J Physiol Heart Circ Physiol 287: H525-H532, 2004; 10.1152/ ajpheart.00058.2004.-The primary cardiac response to ischemic insult is cardiomyocyte hypertrophy, which initiates a genetic program culminating in apoptotic myocyte loss, progressive collagen replacement, and heart failure, a process termed cardiac remodeling. Although a few cardiomyocytes at the peri-infarct region can proliferate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
7

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(91 citation statements)
references
References 26 publications
3
81
0
7
Order By: Relevance
“…In a model of myocardial infarction in bone marrow transplanted mice, histological analysis showed donor-derived endothelial cells in areas of neovascularization at the border zone of the infarct (73). Recently, the degree of myocardial neovascularization and the level of protection against ischemia-induced cardiomyocyte apoptosis in rats have been shown to depend on the absolute numbers of injected angioblasts (74). These experimental data have been strongly supported by clinical observations.…”
Section: Mobilization Of Endothelial Progenitor Cellsmentioning
confidence: 76%
“…In a model of myocardial infarction in bone marrow transplanted mice, histological analysis showed donor-derived endothelial cells in areas of neovascularization at the border zone of the infarct (73). Recently, the degree of myocardial neovascularization and the level of protection against ischemia-induced cardiomyocyte apoptosis in rats have been shown to depend on the absolute numbers of injected angioblasts (74). These experimental data have been strongly supported by clinical observations.…”
Section: Mobilization Of Endothelial Progenitor Cellsmentioning
confidence: 76%
“…Exciting results of the experimental studies have led to clinical studies which demonstrated benefit of the stem cells on left ventricular functions after acute myocardial infarction or ischemic cardiomyopathy (Chachques et al 2004;Schuster et al 2004;Ince et al 2005). Being accepted as an effective and safe way of performing stem cells into infarcted myocardial region, intracoronary infusion has become a preferable route in particularly acute MI patients (Chen et al 2004;Fernandez-Aviles et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was dose dependent and caused regeneration of new myocardium by inducing cardiomyocyte cycling. 34 However, several authors have questioned this process of direct incorporation of BMCs into the vascular wall and instead proposed a different mechanism. 35 The development of new vasculature or collateral vessels could be induced by pro-arteriogenic factors secreted by the transplanted BMCs, possibly by the presence of large numbers of monocytes in these fractions.…”
Section: Myoblastsmentioning
confidence: 99%